Answer:
Step-by-step explanation:
an = a1 * r^(n - 1)
a1 = first term = 5
r = -2
n = nth term of the sequence
so it starts with 5
second term is :
an = a1 * r^(n - 1)......for second term
a2 = 5 * -2^(2 - 1) =
a2 = 5 * -2^1
a2 = 5 * -2
a2 = -10
an = a1 * r^(n - 1)....looking for a3
a3 = 5 * -2^(3 - 1)
a3 = 5 * -2^2
a3 = 5 * 4
a3 = 20
an = a1 * r^(n - 1)....looking for a4
a4 = 5 * -2^(4 - 1)
a4 = 5 * -2^3
a4 = 5 * -8
a4 = - 40
an = a1 * r^(n - 1)...looking for a5
a5 = 5 * -2^(5 - 1)
a5 = 5 * -2^4
a5 = 5 * 16
a5 = 80
an = a1 * r^(n-1)...looking for a6
a6 = 5 * -2^(6 - 1)
a6 = 5 * -2^5
a6 = 5 * -32
a6 = -160